Impact of Road Transport Means on Climate Change and Human Health in Poland - Burchart-Korol, Dorota; Folęga, Piotr (Promet - Traffic&Transportation, 2019)
Operation of means of transport is one of major sources of environmental impact. The goal of this article was to analyse the greenhouse gas emissions and to assess the impact of operation of means of road transport in Poland on human health using the life cycle assessment technique based on an analysis of emission of dust and gas pollutants. Road transport was assessed by taking the following means of transport into account: passenger cars, other cars with weight of up to 3,500 kg, lorries, buses, motorcycles, mopeds and tractors. The analysis covered various dust and gas pollutants, including the emission of CO2, CO, N2O, CH4, NOx, NMVOC, PM and SO2. Using the IMPACT 2002+ life cycle impact assessment method, transport was assessed in a breakdown into the following impact categories: greenhouse gas emission and damage to human health, including damage caused by organic and inorganic compounds. It has been evidenced that the highest emissions of dust and gas pollutants are caused by passenger cars, which is mainly due to the number of vehicles of this type traversing Polish roads. The main cause of climate changes due to road transport is CO2 emission, while NOx emission is the main factor determining individual categories of damage to human health. The negative environmental impact is primarily related to the operation of combustion engine vehicles. Diesel oil and petrol are currently the main fuels used in Polish transport. In order to reduce their impact on the environment one should intensify the efforts aimed at increasing the share of alternative fuels in transport.